Survey study of intestinal parasites on Fresh vegetables collected from some Baghdad Sales and its role in human infection (Baghdad Science Journal, 2013)
Fresh vegetables are an important part of a healthy diet. The consumption of raw vegetables without cooking or good washing can be a major rout of transmission to the parasitic infection. The goal of this study was to determine the intestinal parasitic contamination of fresh vegetables from vegetables sales markets in Baghdad province during the different above months of the year. A total of 303 samples of different vegetables were randomly selected from three wholesale markets distributed through different regions in Baghdad (East, West and South) and then were examined by a floatation method. The present study showed that the collected vegetables were contaminated with 12 species of intestinal parasites, and the total percentage of contamination was 161 (53.1%) . ZnSo4 solution showed the highest percentage of contaminated vegetables (31.2%) while sucrose showed the lowest percentage (8.9%).